2021
DOI: 10.3390/horticulturae7110511
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis in Vitis for Genome Editing: Optimization of Protocols for Recalcitrant Genotypes

Abstract: New Plant Breeding Techniques (NPBTs) protocols have been developed to produce new grape varieties with improved quantitative and qualitative characteristics. Reliable transformation protocols for grapes are based on the generation/induction of embryogenic callus cells that are then transformed. Varieties such as Italia have proven to be very recalcitrant to regeneration via somatic embryogenesis. In this work, the development of a protocol for improved production of embryogenic calluses is described. Two ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…The results determined that all the explants were able to regenerate somatic embryos to a different extent according to the induction medium chosen. Our study demonstrated that full or half-strength MS basal salts worked best for Glera as there was no calli formation on the PIV medium, in contrast with findings from recent similar research performed on the same genotype, where the induction of somatic embryogenesis in various local Italian varieties was obtained using PIV medium (Gambino et al 2007;Forleo et al 2021). Embryogenic calli formation was nil in twelve of the fifteen media tested, and there is no absolute determining factor to explain the induction of embryogenic calli in Glera as the calli formation was somewhat random (embryogenic calli formed on media E, G, and H); the common factor in these three media was the presence of BAP and 2,4-D, in which, the concentration of auxin was double that of cytokinins.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The results determined that all the explants were able to regenerate somatic embryos to a different extent according to the induction medium chosen. Our study demonstrated that full or half-strength MS basal salts worked best for Glera as there was no calli formation on the PIV medium, in contrast with findings from recent similar research performed on the same genotype, where the induction of somatic embryogenesis in various local Italian varieties was obtained using PIV medium (Gambino et al 2007;Forleo et al 2021). Embryogenic calli formation was nil in twelve of the fifteen media tested, and there is no absolute determining factor to explain the induction of embryogenic calli in Glera as the calli formation was somewhat random (embryogenic calli formed on media E, G, and H); the common factor in these three media was the presence of BAP and 2,4-D, in which, the concentration of auxin was double that of cytokinins.…”
Section: Discussioncontrasting
confidence: 68%
“…Our results determined that Glera flower explants showed higher embryogenic potential when cultured on the MS-optimized media, compared to NN-based media. Recent findings from the study by Forleo et al (2021) performed on the same genotype, reported whole flowers as the best explant for somatic embryogenesis induction when initiated on PIV medium. While the optimized composition of the induction media assayed in this study led to individuate pistils as the most responsive starting explant on culture media G and H, enhancing the embryogenic potential of this cultivar.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…There are few available detailed reports on SE in blueberries ( Ghosh et al., 2017 ; Ghosh et al., 2018 ). However, studies are available on SE in grapes ( Nakajima and Matsuta, 2003 ; Dhekney et al, 2016 ; Forleo et al., 2021 ), strawberry ( Biswas et al., 2009 ), Arbutus unedo (strawberry tree; Martins et al, 2022 ) and L. barbarum ( Verma et al., 2022 ) on semisolid media. Reports on SE in berry crops are scarce in a bioreactor system.…”
Section: In Vitro Propagationmentioning
confidence: 99%